The Effectiveness Of The Dedicated Storage Method On Building Layout At PT Puninar Anji Kyk Logistik Indonesia - Rahayu, Ayu Sri; Suprayitno, Degdo (Sinergi International Journal of Logistics, 2023)
This research was conducted at PT Puninar Anji NYK Logistics Indonesia. The purpose of this study is to determine the results of data analysis from the effectiveness of the dedicated storage method on the warehouse layout at PT Puninar Anji NYK Logistics Indonesia. In this study, researchers distributed 30 questionnaires to respondents, and these respondents were directly related to the object of study. The research methodology used in this study is a quantitative research method, with a type of causal associative research, which is research that aims to determine the cause and effect or relationship between two or more variables to control a phenomenon. The results of data calculation and analysis in this study were processed using the SPSS program version 26. From the calculation results using SPSS Version 26, the results of the regression equation were obtained, namely Y = 0.253 + 0.611X. So it can be concluded that the results show that the Dedicated Storage Method can increase the effectiveness of the Warehouse Layout by 61.1%. The result of the R Square (R2) value of 0.830 or with a percentage of 83%, it can be said that the variable Dedicated Storage Method has an influence of 83% on the warehouse layout, and the remaining 17% is the influence of other factors that are not studied by this study. While the test results show a calculated value of 11.708 > ttable of 2.048, with a significance result of 0.000 < 0.05 so that it can be concluded that the variable of the dedicated storage method (X) has a significant effect on the warehouse layout variable (Y). So it can be concluded that H0 is rejected and H1 is accepted, the dedicated storage method is able to increase the effectiveness of the warehouse layout at PT PANLI.